Effect of acid etching time on the degradation of resin-dentin bonds in primary teeth - Sanabe, Mariane Emi; Kantovitz, Kamila Rosamiglia; De Souza, Costa Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (My University, 2009)
To investigate the influence of etching time on the degradation of resin-dentin bonds produced in primary teeth. Methods: 40 primary molars were randomly divided into four groups according to the adhesive system, Single Bond (SB) and Clearfil SE Bond (CSEB), and acid etching time. SB was applied to dentin after phosphoric acid etching for 15 or 7 seconds, whereas CSEB was applied after the application of SE Primer for 20 or 10 seconds. Resin composite crowns were built-up followed by the production of specimens with a cross-sectional area of 0.49 mm 2, which were further divided according to the storage condition, 24 hours, 6 and 12 months in water. Data were submitted to ANOVA and Tukey tests (α=0.05). Results: After 24 hours there was no significant difference between bond strengths produced by the adhesive systems, irrespective of the acid etching time. Water storage for 6 and 12 months significantly reduced bond strengths of SB, especially when the dentin was acid etched for 15 seconds. For CSEB, no significant alteration in bond strength was seen up to the storage period of 12 months for both etching times. (Am J Dent 2009;22:).